Effects of Growth Hormone (GH) Transgene and Nutrition on Growth and Bone Development in Common Carp. Issue 8 (6th June 2013) - Zhu, Tingbing; Zhang, Tanglin; Wang, Yaping; Chen, Yushun; Hu, Wei; Zhu, Zuoyan
ABSTRACT Limited information is available on effects of growth hormone transgene and nutrition on growth and development of aquatic animals. Here, we present a study to test these effects with growth‐enhanced transgenic common carp under two nutritional conditions or feeding rations (i.e., 5% and 10% of fish body weight per day). Compared with the nontransgenic fish, the growth rates of the transgenic fish increased significantly in both feeding rations. The shape of the pharyngeal bone was similar among treatments, but the transgenic fish had relatively smaller and lighter pharyngeal bone compared with the nontransgenic fish. Calcium content of the pharyngeal bone of the transgenic fish was significantly lower than that of the nontransgenic fish. Feeding ration also affected growth rate but less of an effect on bone development. By manipulating intrinsic growth and controlling for both environment (e.g., feeding ration) and genetic background or genotype (e.g., transgenic or not), this study provides empirical evidence that the genotype has a stronger effect than the environment on pharyngeal bone development. The pharyngeal bone strength could be reduced by decreased calcium content and calcification in the transgenic carp. J. Exp. Zool. 319A: 451–460, 2013. © 2013 Wiley Periodicals, Inc.